2019
DOI: 10.1038/s41388-019-0700-2
|View full text |Cite
|
Sign up to set email alerts
|

WNT signaling modulates PD-L1 expression in the stem cell compartment of triple-negative breast cancer

Abstract: Triple-negative breast cancers (TNBCs) are characterized by a poor prognosis and lack of targeted treatments, and thus, new therapeutic strategies are urgently needed. Inhibitors against programmed death-1 (PD-1)/PD-1 ligand (PD-L1) have shown significant efficacy in various solid cancers, but their activity against TNBCs remains limited. Here, we report that human TNBCs molecularly stratified for high levels of PD-L1 (PD-L1High) showed significantly enriched expression of immune and cancer stemness pathways c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
107
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(113 citation statements)
references
References 49 publications
6
107
0
Order By: Relevance
“…In agreement with another group [50], we recently showed that the activation of the WNT signaling pathway increased PD-L1 expression on the plasma membrane of triple-negative breast CSCs (TNBCSCs) [42]. We also provided the first evidence that PD-L1+ TNBCSCs interact with tumorinfiltrating CD8+ and PD-1+ immune cells, thus halting antitumor immune responses [42].…”
Section: Cscs: Leading Actors In the Intratumor Immunosuppressive Scesupporting
confidence: 84%
See 2 more Smart Citations
“…In agreement with another group [50], we recently showed that the activation of the WNT signaling pathway increased PD-L1 expression on the plasma membrane of triple-negative breast CSCs (TNBCSCs) [42]. We also provided the first evidence that PD-L1+ TNBCSCs interact with tumorinfiltrating CD8+ and PD-1+ immune cells, thus halting antitumor immune responses [42].…”
Section: Cscs: Leading Actors In the Intratumor Immunosuppressive Scesupporting
confidence: 84%
“…Specifically, the The recent introduction of monoclonal antibodies (mAbs) targeting the PD-1/PD-L1 signaling axis in cancer therapy significantly improved the survival of patients with different advanced and aggressive tumor types, including melanoma, non-small-cell lung cancer, and kidney carcinoma [49]. In agreement with another group [50], we recently showed that the activation of the WNT signaling pathway increased PD-L1 expression on the plasma membrane of triple-negative breast CSCs (TNBCSCs) [42]. We also provided the first evidence that PD-L1+ TNBCSCs interact with tumor-infiltrating CD8+ and PD-1+ immune cells, thus halting antitumor immune responses [42].…”
Section: Cscs: Leading Actors In the Intratumor Immunosuppressive Scesupporting
confidence: 64%
See 1 more Smart Citation
“…While writing this manuscript, Castagnoli et al 30 and Hsu et al 31 reported a role for Wnt signaling in regulating PD-L1 expression on breast CSCs. We did not see such an effect of the Wnt pathway on PD-L1 expression in our model of CSCs when we used the inhibitor ICG-001, which is supposed to block the Wnt pathway downstream by preventing the CBP/ β-catenin activation.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, it is likely that cisplatin treatment leads to an epithelial cell fate change toward a mesenchymal state (24), which may represent a dedifferentiation process that involves Wnt signaling. Lastly, Wnt signaling has been shown to contribute to immune invasion as well as systemic inflammation in the tumor microenvironment that drives cancer metastasis (42)(43)(44)(45). Whether TcdB FBD may provide a synergistic effect with immunotherapy such as PD-1/PD-L1 antibodies remains to be explored.…”
Section: Tcdb Fbd Synergizes With Cisplatin In Treating Both Bl and Lmentioning
confidence: 99%